2021
DOI: 10.1007/s42764-021-00031-4
|View full text |Cite
|
Sign up to set email alerts
|

SIRT7–SREBP1 restrains cancer cell metabolic reprogramming by upregulating IDH1

Abstract: SIRT7 plays critical roles in tumorigenesis and tumor progression; however, the underlying mechanisms are poorly understood. Here, we aimed to identify downstream targets of SIRT7 to help delineate its precise function. In this study, we demonstrate that SIRT7 is essential to regulate IDH1 expression in various cancer cell types. Interestingly, both SIRT7 and IDH1 levels are downregulated in breast cancer lung metastases and are useful for predicting disease progression and prognosis. Mechanistically, SIRT7 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Conversely, TMZ slightly reduced U118MG tumor g significantly at day 23 (Figure 2C) or at day 18 (Figure S4B), but TMZ did not signifi affect U138MG tumor growth (Figures 2D and S4C). Indeed, both U118MG and U1 have been described as having a low [43,45,46] and unmethylated [43,44] MGMT p respectively, suggesting poor response to TMZ, consistent with our observations.…”
Section: Tmz Affected Gbm In Vivo Tumor Growth Differently In Subcuta...supporting
confidence: 92%
See 1 more Smart Citation
“…Conversely, TMZ slightly reduced U118MG tumor g significantly at day 23 (Figure 2C) or at day 18 (Figure S4B), but TMZ did not signifi affect U138MG tumor growth (Figures 2D and S4C). Indeed, both U118MG and U1 have been described as having a low [43,45,46] and unmethylated [43,44] MGMT p respectively, suggesting poor response to TMZ, consistent with our observations.…”
Section: Tmz Affected Gbm In Vivo Tumor Growth Differently In Subcuta...supporting
confidence: 92%
“…Here, we investigated the effect of TMZ and Fingolimod treatments in GBM in vitro and in vivo models. We used different GBM cell lines, i.e., IDH1wt and MGMT hypermethylated U87MG human cells [ 40 , 41 , 42 , 43 , 44 ], IDH1wt and low MGMT methylated U118MG human cells [ 43 , 45 , 46 ], IDH1wt and unmethylated MGMT U138MG human cells [ 43 , 44 ], and IDH1wt and MGMT hypermethylated GL261 mouse cells recapitulating human GBM features [ 16 , 47 , 48 , 49 , 50 ]. Using in vitro 2D and 3D culture models, we demonstrated that TMZ displayed cytotoxic effects on the four GBM cells tested.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in breast carcinoma, SIRT6 acts as a tumor suppressor [ 85 ], which is correlated with an increased H3K9ac mark resulting in enhanced expression of glycolytic genes [ 86 ]. SIRT7 promotes isocitrate dehydrogenase 1 (IDH1) transcription in a SERPINE1 mRNA binding protein 1 (SERBP1) dependent manner to increase the α-keto-glutarate level and thereby enhance gluconeogenesis and lipogenesis, and destabilize HIF1α, to reverses glycolysis [ 87 ]. Basically, this SIRT7–IDH1 axis works to regulate metabolic reprogramming in cancer cells and, hence can help with therapeutic interventions [ 87 ].…”
Section: Epigenetic Reprogramming Of Metabolic Pathways – a Root Caus...mentioning
confidence: 99%
“…SIRT7 promotes isocitrate dehydrogenase 1 (IDH1) transcription in a SERPINE1 mRNA binding protein 1 (SERBP1) dependent manner to increase the α-keto-glutarate level and thereby enhance gluconeogenesis and lipogenesis, and destabilize HIF1α, to reverses glycolysis [ 87 ]. Basically, this SIRT7–IDH1 axis works to regulate metabolic reprogramming in cancer cells and, hence can help with therapeutic interventions [ 87 ]. Apart from epigenetic enzymes, the roles of different chromatin readers, which regulate metabolic programs, have been investigated.…”
Section: Epigenetic Reprogramming Of Metabolic Pathways – a Root Caus...mentioning
confidence: 99%
“…Further research studies have shown that SIRT7 enhances IDH1 transcription, and that SIRT7 insufficiency downregulates IDH1 expression, resulting in cell metabolic reprogramming during tumorigenesis [ 167 ]. IDH1 mRNA and protein levels were found elevated in primary GB supporting the aggressive tumor growth and therapy resistance, while IDH1 inactivation promoted apoptosis and enhanced response to targeted therapies [ 168 ].…”
Section: Evidence Of Sirts Implication In Gb Pathogenesismentioning
confidence: 99%